Analisis Tindak Tutur pada Wawancara Presiden Prabowo Bersama Enam Jurnalis pada Youtube Najwa Shihab (Kajian Pragmatik) - Yuwafa Faurelio Yahya; Adila Nisa Hamidah; Taswirul Afkhar (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study analyzes President Prabowo's speech acts in an interview with six journalists and editors-in-chief on the program